Preparation method and application of nano zero-valent iron-zeolite core-shell structure composite material

By forming a zeolite core-shell structure on the surface of nano zero-valent iron, forming a nano zero-valent iron-zeolite core-shell structure composite, the problems of easy agglomeration of nZVI in water and rapid release of Fe2+ are solved, and efficient degradation of trichlorophenol and Long-term repair effect.

CN119386921APending Publication Date: 2025-02-07NORTHEAST AGRICULTURAL UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411501099.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Nano-zero-valent iron (nZVI) is prone to agglomeration when used in water bodies, resulting in low reactivity. The rapid release of Fe2+ will quench free radicals, making it difficult to effectively degrade organic pollutants.

Method used

By generating a zeolite core-shell structure on the surface of nano zero-valent iron, a nano zero-valent iron-zeolite core-shell structure composite material is formed, and the mass ratio of zeolite and nano zero-valent iron is controlled to prevent iron oxides from being generated on the nZVI surface and slow down the release of Fe2+ Speed, prolong electron release time, and form long and stable activated persulfate.

Benefits of technology

It effectively prevents the agglomeration of nZVI and the rapid release of Fe2+, improves the reaction activity, promotes the efficient degradation of trichlorophenol, and has a wide range of pH adaptability and sustained release effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386921A_ABST
    Figure CN119386921A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a nano zero-valent iron-zeolite core-shell structure composite material, and relates to the technical field of nano zero-valent iron composite material preparation. A layer of zeolite core-shell structure is generated on the surface of the nano zero-valent iron to prevent iron oxide from being generated on the surface of nZVI to reduce the reaction activity, and meanwhile, the mass ratio of zeolite / zero-valent iron strongly affects gradual release of Fe < 2 + > in the nano zero-valent iron-zeolite core-shell structure composite material, so that iron core oxidation is slowed down, and the reaction activity of nZVI is improved. The release speed of electrons is also slowed down, the gradually released electrons form a long-time and stable activation effect on persulfate, and the degradation of trichlorophenol can be promoted. According to the preparation method and application of the nano zero-valent iron-zeolite core-shell structure composite material, the nano zero-valent iron-zeolite core-shell structure composite material can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of nano zero-valent iron composite materials, and in particular to a preparation method and application of a nano zero-valent iron-zeolite core-shell structure composite material. Background Art

[0002] With the continuous advancement of urbanization and industrialization, more and more antibiotics, fungicides and herbicides are put into use in production and life. These organic pollutants have seriously damaged the ecological environment. Trichlorophenol, as a highly toxic organic substance, is easily soluble in organic solvents such as alcohol and ether. Trichlorophenol is mainly used as a fungicide, preservative or solvent for polyester fibers. Wastewater discharged from the polyester fiber recycling process in industrial activities and the spraying of preservatives on materials such as wood and pulp used in human life cause trichlorophenol to enter water bodies and soil. It can be absorbed through the skin and cause poisoning, which seriously threatens human health and ecological safety. Therefore, it is urgent to efficiently repair the trichlorophenol pollution in the environment.

[0003] At present, there are many methods to solve organic pollution, such as physical adsorption, chemical oxidation, microbial and plant remediation, etc. Among them, advanced oxidation technology has become one of the most widely used environmental pollution remediation methods due to its simplicity, high efficiency and non-toxic or low-toxic degradation products, including traditional Fenton oxidation technology and persulfate-based oxidation technology, among which persulfate-based oxidation technology often uses carbon-based materials or iron-based materials as catalysts to activate persulfate to degrade pollutants.

[0004] Compared with other iron-based materials, nano-zero-valent iron (nZVI) has advantages such as high reactivity and large specific surface area, but nZVI also has obvious limitations in practical applications. First, the magnetic attraction of nZVI makes it easy for particles to agglomerate, making it difficult to migrate in water, resulting in low reactivity; in addition, Fe is quickly released into the solution by nZVI. 2+ It will quench the generated free radicals, making it difficult for the pollutants to be effectively degraded.

[0005] In order to solve the above problems, the commonly used modification methods include porous material (such as biochar) loading, sulfurization modification, surfactant coating, etc. Among them, by using silicon dioxide to coat nZVI with zeolite, a zeolite coating can be formed on the surface of nZVI, which effectively solves the problems of nZVI easy agglomeration and Fe 2+ However, according to previous literature reports, the commonly used The preparation method of nZVI coated with silica is relatively complicated, the reaction conditions are difficult to control, and different preparation conditions and proportions have a great influence on the reactivity of nZVI. In view of the above problems, it is urgent to find a modification method that is simple in preparation and can solve the above defects of nZVI, and then apply it to the degradation of organic pollutants. Summary of the invention

[0006] The purpose of the present invention is to solve the above technical problems and to provide a preparation method and application of a nano zero-valent iron-zeolite core-shell structure composite material.

[0007] A method for preparing a nano zero-valent iron-zeolite core-shell structure composite material is carried out according to the following steps:

[0008] Step S1: preparing nano zero-valent iron;

[0009] In a nitrogen environment, FeCl2·4H2O is added to distilled water and stirred thoroughly to obtain a clear solution a; NaBH4 solution is injected into the clear solution a, and stirring is continued after the injection is completed, and then separation is performed to obtain a solid b, and finally, after washing and vacuum freeze-drying, nano zero-valent iron is obtained;

[0010] Step S2: preparing a nano zero-valent iron-zeolite core-shell structure composite material;

[0011] The nanometer zero-valent iron obtained in step S1 is sieved, then immersed in silica sol, and then zeolite is added; after being evenly mixed, the mixture is separated and dried, placed in a tube furnace, heated to 340-360° C., and calcined at a temperature of 340-360° C. for 410-430 min, and finally sieved to obtain a nanometer zero-valent iron-zeolite core-shell structure composite material;

[0012] The mass ratio of the zeolite to the nanometer zero-valent iron is (2:1), (1:1), (1:2), (1:3) or (1:4).

[0013] An application of a nanometer zero-valent iron-zeolite core-shell structure composite material, and the application of the nanometer zero-valent iron-zeolite core-shell structure composite material in removing trichlorophenol in water.

[0014] Beneficial effects of the present invention:

[0015] (1) The present invention prepares a nano zero-valent iron-zeolite core-shell structure composite material by effectively controlling the mass ratio of zeolite and nano zero-valent iron. Specifically, a layer of zeolite core-shell structure is generated on the surface of nano zero-valent iron to prevent the generation of iron oxides on the surface of nZVI, thereby reducing its reaction activity. At the same time, the mass ratio of zeolite / zero-valent iron strongly affects the Fe content in the nano zero-valent iron-zeolite core-shell structure composite material. 2+ The gradual release of electrons not only slows down the oxidation of the iron core, but also slows down the release rate of electrons. The gradually released electrons form a long-term and stable activation effect on persulfate, which can promote the degradation of trichlorophenol.

[0016] (2) The present invention provides an organic pollutant remediation agent that can be applied to water bodies. The nano zero-valent iron-zeolite core-shell structure composite material has almost no effect on the degradation of trichlorophenol in the range of 25 to 45°C, and has a wide adaptability to pH. At the same time, compared with other remediation agents, it has a certain sustained-release effect, which can not only achieve efficient degradation of trichlorophenol in water bodies but also has a long-term effect, thereby promoting the development and application of organic pollutant remediation agents in water bodies.

[0017] The invention can obtain a preparation method and application of a nano zero-valent iron-zeolite core-shell structure composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A graph showing the effect of the nano zero-valent iron-zeolite core-shell structure composite material prepared by using different mass ratios of zeolite and zero-valent iron in Examples 1-5 on the degradation rate of trichlorophenol;

[0019] Figure 2 A high-resolution transmission electron microscopy image showing the nano zero-valent iron-zeolite core-shell structure composite material in Example 1;

[0020] Figure 3 An element mapping diagram showing the superposition of the nano zero-valent iron-zeolite core-shell structure composite material in Example 1;

[0021] Figure 4 The figure shows the effect of different dosages of the repair agent (50, 80, 100, 150 mg / L) on the degradation rate of trichlorophenol in Example 1;

[0022] Figure 5 The figure shows the effect of different persulfate dosages (0.3, 0.5, 0.8, 1.0, 1.5 mM) on the degradation rate in Example 1;

[0023] Figure 6 The figure shows the effect of different pH values ​​(pH=3, 5, 7, 9) on the degradation rate of trichlorophenol in Example 1;

[0024] Figure 7 The figure shows the effect of different temperatures (25, 35, 45° C.) on the degradation rate of trichlorophenol in Example 1;

[0025] Figure 8 The figure shows the effect of using different quenchers to quench active species on the degradation rate of trichlorophenol in Example 1. DETAILED DESCRIPTION

[0026] Specific implementation method 1: This implementation method is a method for preparing a nano zero-valent iron-zeolite core-shell structure composite material, which is carried out according to the following steps:

[0027] Step S1: preparing nano zero-valent iron;

[0028] In a nitrogen environment, FeCl2·4H2O is added to distilled water and stirred thoroughly to obtain a clear solution a; NaBH4 solution is injected into the clear solution a, and stirring is continued after the injection is completed, and then separation is performed to obtain a solid b, and finally, after washing and vacuum freeze-drying, nano zero-valent iron is obtained;

[0029] Step S2: preparing a nano zero-valent iron-zeolite core-shell structure composite material;

[0030] The nanometer zero-valent iron obtained in step S1 is sieved, then immersed in silica sol, and then zeolite is added; after being evenly mixed, the mixture is separated and dried, placed in a tube furnace, heated to 340-360° C., and calcined at a temperature of 340-360° C. for 410-430 min, and finally sieved to obtain a nanometer zero-valent iron-zeolite core-shell structure composite material;

[0031] The mass ratio of the zeolite to the nanometer zero-valent iron is (2:1), (1:1), (1:2), (1:3) or (1:4).

[0032] Specific embodiment 2: The difference between this embodiment and specific embodiment 1 is that in step S1, FeCl2·4H2O is added to distilled water and mechanically stirred at a speed of 250-300 rpm for 25-35 min. The ratio of the mass of FeCl2·4H2O to the volume of distilled water is (3.45-3.55) g: 200 mL.

[0033] The other steps are the same as those in the first specific implementation.

[0034] Specific implementation method three: The difference between this implementation method and specific implementation method one or two is that in step S1, before adding FeCl2·4H2O to distilled water, nitrogen is first passed for 25 to 30 minutes.

[0035] The other steps are the same as those in the first or second embodiment.

[0036] Specific embodiment 4: The difference between this embodiment and specific embodiments 1 to 3 is that in step S1, NaBH4 solution is injected into the clear solution a at a speed of 8 to 10 mL / min, and stirring is continued for 25 to 35 min after the injection is completed.

[0037] The other steps are the same as those in Specific Embodiments 1 to 3.

[0038] Specific implementation method five: The difference between this implementation method and specific implementation methods one to four is that: in step S1, a peristaltic pump is used to inject NaBH4 solution into the clear solution a; in step S1, magnetic means are used for separation.

[0039] The other steps are the same as those in Specific Embodiments 1 to 4.

[0040] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the ratio of the mass of NaBH4 to the volume of water in the NaBH4 solution described in step S1 is (3.62-3.72) g:50 mL.

[0041] The other steps are the same as those in Specific Embodiments 1 to 5.

[0042] Specific embodiment 7: The difference between this embodiment and specific embodiments 1 to 6 is that in step S1, the solid b is washed with anhydrous ethanol and oxygen-free water in sequence.

[0043] The other steps are the same as those in Specific Embodiments 1 to 6.

[0044] Specific embodiment eight: The difference between this embodiment and specific embodiments one to seven is that in step S2, the nano zero-valent iron is passed through a 30-40 mesh sieve and then immersed in a silica sol with a concentration of 30%.

[0045] The other steps are the same as those in Specific Embodiments 1 to 7.

[0046] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that in step S2, the temperature is heated to 340-360°C at a heating rate of 7-10°C / min.

[0047] The other steps are the same as those in Specific Embodiments 1 to 8.

[0048] Specific implementation method ten: This implementation method is an application of a nano zero-valent iron-zeolite core-shell structure composite material, and the application of the nano zero-valent iron-zeolite core-shell structure composite material in removing trichlorophenol in water.

[0049] The following examples are used to verify the beneficial effects of the present invention:

[0050] Example 1: A method for preparing a nano zero-valent iron-zeolite core-shell structure composite material, comprising the following steps:

[0051] Step S1: preparing nano zero-valent iron;

[0052] First, nitrogen was introduced into distilled water for 30 minutes, and then 3.55 g of FeCl2·4H2O was added to 200 mL of distilled water, and mechanically stirred at a speed of 300 rpm for 30 minutes to obtain a clear solution a; NaBH4 solution was injected into the clear solution a at a speed of 10 mL / min using a peristaltic pump, and stirring was continued for 30 minutes after the injection was completed, and then magnetic means were used for separation to obtain solid b, and finally anhydrous ethanol and oxygen-free water were used for washing in turn, and then vacuum freeze-dried to obtain nano zero-valent iron;

[0053] The ratio of the mass of NaBH4 to the volume of water in the NaBH4 solution is 3.62 g:50 mL;

[0054] Step S2: preparing a nano zero-valent iron-zeolite core-shell structure composite material;

[0055] The nano zero-valent iron obtained in step S1 is passed through a 30-mesh sieve, then immersed in a silica sol with a concentration of 30%, and then zeolite is added; the mixture is manually and evenly mixed in a round-bottom flask, and the mixture is separated and dried, and then placed in a tube furnace, heated to 350° C. at a heating rate of 10° C. / min, and calcined at 350° C. for 420 min, and finally sieved to obtain a nano zero-valent iron-zeolite core-shell structure composite material;

[0056] The mass ratio of the zeolite to the nanometer zero-valent iron is 1:3.

[0057] Example 2: In this example, the mass ratio of zeolite to nano-zero-valent iron is 2:1; other experimental conditions are the same as those in Example 1.

[0058] Example 3: In this example, the mass ratio of zeolite to nano-zero-valent iron is 1:1; other experimental conditions are the same as those in Example 1.

[0059] Example 4: In this example, the mass ratio of zeolite to nano-zero-valent iron is 1:2; other experimental conditions are the same as those in Example 1.

[0060] Example 5: In this example, the mass ratio of zeolite to nano-zero-valent iron is 1:4; other experimental conditions are the same as those in Example 1.

[0061] Using the nano zero-valent iron-zeolite core-shell structure material prepared in the above embodiment, material ratio optimization experiments and trichlorophenol degradation experiments in water under different conditions were carried out, and the specific conclusions are as follows:

[0062] 1. Material selection:

[0063] The adsorption process is: use a balance to weigh 0.01±0.002g of nano-zero-valent iron-zeolite core-shell structure material with different nano-zero-valent iron / zeolite mass ratios, add it to a 150mL conical flask, then add 100mL of 20mg / L trichlorophenol solution and 1mM persulfate to the conical flask, shake at 200rpm, measure the concentration of trichlorophenol in the solution at 5, 10, 15, 20, and 30min, respectively, and calculate the removal rate of the material.

[0064] Figure 1 The figure shows the effect of the nano zero-valent iron-zeolite core-shell structure composite material prepared by using different mass ratios of zeolite and zero-valent iron in Examples 1-5 on the degradation rate of trichlorophenol; Figure 1As shown in the figure, zeolite alone has almost no degradation effect on trichlorophenol in water, and nZVI alone has a degradation rate of only 56.20% for trichlorophenol. This is because the electron release rate is too fast, resulting in the quenching of the generated free radicals, which cannot effectively degrade trichlorophenol. As the zeolite / zero-valent iron mass ratio increases from 1:4 to 1:3, Fe 2+ The release rate slowed down, fully activating the persulfate and increasing the degradation rate of trichlorophenol to 100%. However, when the zeolite / zero-valent iron mass ratio was further increased to 2:1, the degradation efficiency of trichlorophenol was inhibited to 81.47%. This is because the nZVI coated with too thick zeolite shell limits the Fe 2+ For different zeolite / zero-valent iron mass ratios, as the zeolite / zero-valent iron mass ratio gradually increases, the degradation rate of trichlorophenol gradually increases, but after exceeding a certain range, the degradation rate decreases instead.

[0065] 2. Characterization (high-resolution transmission electron microscopy and elemental mapping):

[0066] Figure 2 The high-resolution transmission electron microscopy image of the nano zero-valent iron-zeolite core-shell structure composite material in Example 1 is shown; Figure 2 As shown, the particle size of nZVI after zeolite coating is 60±10 nm, the edge range is 5-10 nm, and it is irregularly serrated, forming a zeolite-coated core-shell structure.

[0067] Figure 3 Element mapping diagram showing the superposition of the nano zero-valent iron-zeolite core-shell structure composite material in Example 1; Figure 3 As shown, O, Si and Al elements are more distributed on the shell structure, which indicates that a zeolite core-shell structure is formed on the surface of nZVI instead of the original iron oxide.

[0068] 3. The influence of different material dosage:

[0069] The degradation process is: within 0 to 30 minutes, the concentration of trichlorophenol contaminated liquid with a concentration of 20 mg / L is measured at intervals at 25°C, pH=5, and a persulfate dosage of 1.0 mM.

[0070] Figure 4 The figure shows the effect of different dosages of the repair agent (50, 80, 100, 150 mg / L) on the degradation rate of trichlorophenol in Example 1; Figure 4 As shown, when the material dosage is 100 mg / L, the degradation rate of trichlorophenol in water reaches 100%, indicating that 100 mg / L of material can completely activate persulfate to achieve the highest degradation rate. When the material dosage continues to increase to 150 mg / L, persulfate cannot release more active substances and can only shorten the time required for degradation. Therefore, the material dosage is selected to be 100 mg / L.

[0071] 4. Effect of different persulfate dosages:

[0072] The degradation process is: within 0-30 minutes, the concentration of trichlorophenol contaminated liquid with a concentration of 20 mg / L is measured at intervals at 25°C, pH=5, and the material dosage is 100 mg / L.

[0073] Figure 5 The figure shows the effect of different persulfate dosages (0.3, 0.5, 0.8, 1.0, 1.5 mM) on the degradation rate in Example 1; Figure 5 As shown, when the persulfate dosage is 1.0 mM, the degradation rate of trichlorophenol in the water body reaches 100%, indicating that 100 mg / L of material can completely activate 1.0 mM persulfate to release active oxygen species to degrade trichlorophenol. When the persulfate dosage continues to increase to 1.5 mM, there is no more material in the system for activating persulfate, so the persulfate dosage is selected to be 1.0 mM.

[0074] 5. Effect of different pH:

[0075] The degradation process is: within 0-30 minutes, the concentration of trichlorophenol contaminated liquid with a concentration of 20 mg / L is measured at intervals at 25°C, the material dosage is 100 mg / L, and the persulfate dosage is 1.0 mM.

[0076] Figure 6 The figure shows the effect of different pH values ​​(pH=3, 5, 7, 9) on the degradation rate of trichlorophenol in Example 1; Figure 6 As shown in the figure, when pH < 7, the degradation rate of trichlorophenol in water increases with the increase of pH; when pH > 7, Fe(II) forms precipitation under alkaline conditions, causing the degradation rate of trichlorophenol in water to drop to 25.09%. In the range of pH = 3-7, the degradation rate can reach more than 95%, which shows that the system has strong tolerance to pH.

[0077] 6. The influence of different temperatures:

[0078] The degradation process is: within 0-30 minutes, the concentration of trichlorophenol contaminated liquid with a concentration of 20 mg / L is measured at intervals under the conditions of material dosage of 100 mg / L, persulfate dosage of 1.0 mM, and pH = 5.

[0079] Figure 7 The figure shows the influence of different temperatures (25, 35, 45°C) on the degradation rate of trichlorophenol in Example 1; Figure 7As shown in the figure, under three different temperature conditions, the degradation rate of trichlorophenol in water by nano zero-valent iron-zeolite core-shell structure composite material can reach 100%. Not only is the reaction activity of nano zero-valent iron higher under high temperature conditions, but high temperature conditions will also accelerate the activation rate of persulfate, resulting in the time required for complete degradation shortening with increasing temperature. In summary, the nano zero-valent iron-zeolite core-shell structure composite material is a highly efficient repair agent for degrading trichlorophenol in water.

[0080] 7. Active species quenching experiment:

[0081] The degradation process is: within 0 to 30 minutes, the concentration of trichlorophenol contaminated liquid with a concentration of 20 mg / L is measured at intervals at 25°C, the material dosage is 100 mg / L, and the persulfate dosage is 1.0 mM.

[0082] Figure 8 The figure shows the effect of using different quenchers to quench the active species on the degradation rate of trichlorophenol in Example 1, using different concentrations of p-benzoquinone, furfuryl alcohol, methanol and tert-butyl alcohol respectively; Figure 8 As shown, the quenching effect of superoxide radicals by using 10, 25, and 50 mM p-benzoquinone is very significant, making the degradation rate of trichlorophenol in the water extremely low, almost zero, indicating that superoxide radicals may be the main active species in this system. Using 10, 25, and 50 mM FFA to quench singlet oxygen, it was found that the degradation rate of trichlorophenol in the water was greatly reduced, but there was still a certain degree of degradation, indicating that singlet oxygen participated in the reaction in this system. Using 100, 200, 500, and 1000 mM MeOH to quench sulfate radicals and hydroxyl radicals, it was found that the degradation rate of trichlorophenol in the water was greatly reduced, but there was still a certain degree of degradation, indicating that sulfate radicals and hydroxyl radicals participated in the reaction in this system. Using 100, 200, 500, and 1000 mM TBA to quench hydroxyl radicals, it was found that the degradation rate of trichlorophenol in the water was reduced, further verifying the presence of hydroxyl radicals in this system. In summary, superoxide radicals may be the main active species in the system of nano zero-valent iron-zeolite core-shell structure composite material / persulfate degradation of trichlorophenol, and there may be mutual transformation between free radicals and non-free radicals.

Claims

1. A method for preparing a nano zero-valent iron-zeolite core-shell structure composite material, characterized in that The preparation method is carried out according to the following steps: Step S1: preparing nano zero-valent iron; In a nitrogen environment, FeCl2·4H2O is added to distilled water and stirred thoroughly to obtain a clear solution a; NaBH4 solution is injected into the clear solution a, and stirring is continued after the injection is completed, and then separation is performed to obtain a solid b, and finally, after washing and vacuum freeze-drying, nano zero-valent iron is obtained; Step S2: preparing a nano zero-valent iron-zeolite core-shell structure composite material; The nanometer zero-valent iron obtained in step S1 is sieved, then immersed in silica sol, and then zeolite is added; after being evenly mixed, the mixture is separated and dried, placed in a tube furnace, heated to 340-360° C., and calcined at a temperature of 340-360° C. for 410-430 min, and finally sieved to obtain a nanometer zero-valent iron-zeolite core-shell structure composite material; The mass ratio of the zeolite to the nanometer zero-valent iron is (2:1), (1:1), (1:2), (1:3) or (1:4).

2. The method for preparing a nano zero-valent iron-zeolite core-shell structure composite material according to claim 1, characterized in that In step S1, FeCl2·4H2O is added to distilled water and mechanically stirred at a rotation speed of 250-300 rpm for 25-35 min. The ratio of the mass of FeCl2·4H2O to the volume of distilled water is (3.45-3.55) g: 200 mL.

3. The method for preparing a nano zero-valent iron-zeolite core-shell structure composite material according to claim 1 or 2, characterized in that Step S1: Before adding FeCl2·4H2O into distilled water, nitrogen is passed through for 25 to 30 minutes.

4. The method for preparing a nano zero-valent iron-zeolite core-shell structure composite material according to claim 1, characterized in that In step S1, NaBH4 solution is injected into the clear solution a at a rate of 8 to 10 mL / min, and stirring is continued for 25 to 35 min after the injection is completed.

5. The method for preparing a nano zero-valent iron-zeolite core-shell structure composite material according to claim 1 or 4, characterized in that In step S1, a peristaltic pump is used to inject NaBH4 solution into the clear solution a; in step S1, magnetic means are used for separation.

6. The method for preparing a nano zero-valent iron-zeolite core-shell structure composite material according to claim 1 or 4, characterized in that The ratio of the mass of NaBH4 to the volume of water in the NaBH4 solution described in step S1 is (3.62-3.72) g:50 mL.

7. The method for preparing a nano zero-valent iron-zeolite core-shell structure composite material according to claim 1, characterized in that In step S1, the solid material b is washed with anhydrous ethanol and oxygen-free water in sequence.

8. The method for preparing a nano zero-valent iron-zeolite core-shell structure composite material according to claim 1, characterized in that In step S2, the nanometer zero-valent iron is passed through a 30-40 mesh sieve and then immersed in a silica sol with a concentration of 30%.

9. The method for preparing a nano zero-valent iron-zeolite core-shell structure composite material according to claim 1, characterized in that In step S2, the temperature is heated to 340-360°C at a heating rate of 7-10°C / min.

10. Use of a nano zero-valent iron-zeolite core-shell structure composite material prepared by the method according to any one of claims 1 to 9, characterized in that The nano zero-valent iron-zeolite core-shell structure composite material is used to remove trichlorophenol in water.

Citation Information

Cited By

  • Biological-friendly zeolite / nano zero-valent iron composite material as well as preparation method and application thereof

    CN120589928A

  • Preparation method and application of zero-valent iron-based composite material

    CN121422970A